2015
DOI: 10.1099/jmm.0.000106
|View full text |Cite
|
Sign up to set email alerts
|

The synergy of berberine chloride and totarol against Staphylococcus aureus grown in planktonic and biofilm cultures

Abstract: Staphylococcus aureus (S. aureus) is commonly associated with hospital-acquired infections and is known to form biofilms. Bacteria inside biofilms display an increased resistance to chemotherapeutics and host immune defences. Efficient antibiotics or combination therapy are urgently needed to treat patients with biofilm-associated MRSA infections. The objective of the current study was to evaluate the in vitro antimicrobial activities of totarol alone or in combination with berberine chloride (BBR) against S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Several reports displayed that both AZM and BER could target efflux pumps (MexXY) [40, 45] and eDNA [26, 30] in PA. However, macrolides were supposed to be difficult of diffusion across the outer membrane of most gram-negative bacteria [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports displayed that both AZM and BER could target efflux pumps (MexXY) [40, 45] and eDNA [26, 30] in PA. However, macrolides were supposed to be difficult of diffusion across the outer membrane of most gram-negative bacteria [46].…”
Section: Discussionmentioning
confidence: 99%
“…Berberine (BER), a natural isoquinoline alkaloid found in a variety of medicinal plants, had a broad antimicrobial spectrum alone or in combination with other antibiotics [26-28]. The present study aimed to investigate the antibacterial potentials and associated mechanisms of BER and AZM alone and in combination against clinical PA isolates from CF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus, a notorious pathogen, can secrete several exotoxins, such as α-hemolysin, enterotoxins, coagulase, and protein A, all of which may be capable of causing a series of acute and chronic infections, such as infective endocarditis and osteomyelitis, and is a frequent invader in chronic lung disease [1,2]. Furthermore, it has been reported to be a serious threat owing to the appearance of multidrug-resistant strains, such as methicillinresistant S. aureus and vancomycin-methicillin-resistant S. aureus [3].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this IMP resistance in P. aeruginosa novel antibacterial agents are urgently required. Berberine (BEB), a natural isoquinoline alkaloid, is prevalent in numerous medicinal plants and has been demonstrated to have antibacterial and antifungal activities alone or in combination with other drugs (9)(10)(11)(12)(13). In a previous study, BEB was reported to be a potential inhibitor of MexXY-mediated resistance in P. aeruginosa (14).…”
Section: Introductionmentioning
confidence: 99%